AN OVERVIEW OF THE KNOWLEDGE OF YOUNG WOMAN ABOUT EARLY MARRIAGE IN CLASS X.IS SENIOR HIGH SCHOOL 2 BULUKUMBA - Jusni; Dewi Permatasari; Rismayanti; Riska Y (JMNS, 2019)
Knowledge of the impact of early marriage will help adolescents as the nation's future youth to be better able to organize their lives by taking the right steps. Early marriage occurs in adolescents with an age range under 20 years of age. This study aims to determine the knowledge of young women about early marriage in SMA Negeri 2 Bulukumba. This research is a descriptive study. The sample in this study were all 49 students of class X IS obtained by total sampling. Based on the results of the research on the description of the knowledge of young women about early marriage in SMA Negeri 2 Bulukumba through three aspects, namely understanding, causes and impacts. Based on the understanding of 49 respondents, 21 respondents (42.8%) wrote good knowledge, then 28 respondents (57.2%) who had sufficient knowledge and 0 respondents (0%) who had less knowledge indicated that the respondents' knowledge was in the good category. II respondents (22.4%) have good knowledge, then 36 respondents (73.5%) who have sufficient knowledge and 2 respondents (4.1%) who have less knowledge, this shows that the respondents' knowledge is in the sufficient category. Based on the impact of 49 respondents, 27 respondents (55.1%) who had good knowledge, 20 respondents (40.8%) who had sufficient knowledge and 2 respondents (4.1%) who had less knowledge, showed that the respondents' knowledge was in the good category.